2011
DOI: 10.1103/physreva.83.053421
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-duration dependence of the isotopic effect in simple molecular ions driven by strong laser fields

Abstract: In this paper we discuss isotopic effects in simple molecular ions subjected to strong laser fields. We show that the intensity of the emitted spectra strongly depends upon both the nuclear mass of the molecular ions and the laser pulse duration. In particular, for short pulse duration [up to 8 optical cycles (o.c.)], we confirm the trend described in the most studied case in which the high-order harmonic generation is more efficient for heavier isotopes; in contrast, an interesting physical phenomenon is pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Instead, the description of laser-molecule interaction with respect to atoms requires a larger number of free parameters and other effects are observed in addition to those mentioned above, such as Coulomb explosion [16,17], dissociation by means of multiphoton absorption [18] and the enhancement of the ionization probability when the internuclear distance is greater than the equilibrium distance [19]. Furthermore, as shown in [20][21][22][23][24][25][26][27][28][29][30][31][32][33], the nuclear dynamics must be taken into account since significant modifications are evident in the electron dynamics and emitted spectra. Further investigations have also shown that the motion of the nuclei strongly affects the spectrum of the emitted radiation and can be used as an efficient spectrographic tool [21,22,29,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the description of laser-molecule interaction with respect to atoms requires a larger number of free parameters and other effects are observed in addition to those mentioned above, such as Coulomb explosion [16,17], dissociation by means of multiphoton absorption [18] and the enhancement of the ionization probability when the internuclear distance is greater than the equilibrium distance [19]. Furthermore, as shown in [20][21][22][23][24][25][26][27][28][29][30][31][32][33], the nuclear dynamics must be taken into account since significant modifications are evident in the electron dynamics and emitted spectra. Further investigations have also shown that the motion of the nuclei strongly affects the spectrum of the emitted radiation and can be used as an efficient spectrographic tool [21,22,29,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%